Neighborhood Disadvantage and Adult Alcohol Outcomes: Differential Risk by Race and Gender - Karriker-Jaffe, Katherine J. (Rutgers University, 2012)
OBJECTIVE: We examined whether relationships of neighborhood disadvantage with drinker status, heavy drinking, alcohol-related consequences, and dependence differed by race and/or gender. We hypothesized that neighborhood disadvantage would be negatively associated with drinker status but positively associated with heavy and problem drinking, with more pronounced relationships among African American and Hispanic men than other groups. METHOD: Data consisted of nationally representative, randomly selected, cross-sectional samples of White, African American, and Hispanic adults (N = 13,864, of which 52% were female; with 7,493 drinkers, of which 48% were female) from the 2000 and 2005 National Alcohol Surveys merged with 2000 Census data. Analyses included logistic and linear regression using weights to adjust for sampling and nonresponse. RESULTS: Hypotheses were partly supported. Bivariate relationships were in the expected direction. Multivariate main effect models showed that neighborhood disadvantage was significantly associated with increased abstinence and marginally associated with increased negative consequences experienced by drinkers, but race/ethnicity and gender modified these associations. Disadvantage was significantly associated with increased abstinence for all groups except African American and Hispanic men. Among drinkers, disadvantage was significantly negatively associated with heavy drinking by Whites but significantly positively associated with heavy drinking by African Americans. Disadvantage also was associated with elevated alcohol-related consequences for White women and African American men. CONCLUSIONS: The findings have implications for the development of targeted interventions to reduce the unequal impacts of neighborhood disadvantage on alcohol outcomes. Future research should examine the contribution of multiple types of disadvantage to heavy drinking and alcohol problems.